Excessive formation of hydroxyl radicals and aldehydic lipid peroxidation products in cultured skin fibroblasts from patients with complex I deficiency. - Luo, X (1997)
Previous studies suggest oxygen free radicals' involvement in the etiology of cardiomyopathy with cataracts. To investigate the role of free radicals in the pathogenesis of the cardiomyopathy with cataracts and complex I deficiency, fibroblasts from patients were assessed for hydroxyl radical formation and aldehydic lipid peroxidation products with and without redox active agents that increase free radicals. The rate of hydroxyl radical formation in patient cells was increased over 2-10-fold under basal conditions, and up to 20-fold after menadione or doxorubicin treatment compared with normal cells. We also found an overproduction of aldehydes in patient cells both under basal conditions and after treatment. Both hydroxyl radicals and toxic aldehydes such as hexanal, 4-hydroxynon-2-enal, and malondialdehyde were elevated in cells from patients with three types of complex I deficiency. In contrast, acyloins, the less toxic conjugated products of pyruvate and saturated aldehydes, were lower in the patient cells. Our data provide direct evidence for the first time that complex I deficiency is associated with excessive production of hydroxyl radicals and lipid peroxidation. The resultant damage may contribute to the early onset of cardiomyopathy and cataracts and death in early infancy in affected patients with this disease.